Studi komparatif afek positif: VR 360° noninteraktif berbasis alam dan audio alam - Syahvina, Khasya Cantiqa; Hijrianti, Udi Rosida; Ahmad, Miqdad Daly (Jurnal Psikologi Ulayat, 2026)
The increasing problem of mental health in Indonesia necessitates effective preventive strategies, one of which is through increasing positive affect. Interaction with nature has been shown to increase positive affect, but limited access to direct contact with nature poses a challenge. This study examined the difference in affect between non-interactive 360° nature VR and nature audio as alternative replacements for nature. The quantitative quasi-experimental method with post-test only design was conducted. Participants were recruited using purposive sampling techniques who involved 24 subjects divided into two experimental groups: non-interactive 360° VR nature and nature audio with each group consisting of 12 subjects aged 19–23 years without visual or hearing impairments and a history of motion sickness. The instruments used are Shinecon 6.0 VR, nature audio, and the adapted PANAS scale. The results showed a significant difference in affect, with higher positive affect scores in the 360° VR group compared to the audio group. These findings suggest that non-interactive 360° nature-based VR may serve as a promising alternative intervention to enhance positive affect in populations with limited access to natural environments.